2005
DOI: 10.1111/j.1365-3156.2005.01404.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary care nurses using guidelines in Thailand: a randomized controlled trial

Abstract: Summarybackground Nurses run primary health centres in Thailand. We examined whether clinical guidelines improved the quality of the care they provide.methods Eighteen nurse-led health centres randomized to (a) guidelines, receiving a training workshop plus educational outreach visit, with guidelines for children (acute respiratory tract infection and diarrhoea) and adults (diazepam prescribing and diabetes management) or (b) usual care. Outcomes were changes at 6 months in antibiotic use, diazepam prescribing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 14 publications
0
49
0
Order By: Relevance
“…The ICD-10 training kit, an educational training programme and materials produced by the WHOImplementation strategies therefore comprised: educational meetings and educational materialsGP’s attitudes, knowledge, interview skills and ability for diagnosing psychiatric disorders in a primary care settingThere was statistically significant improvement in GP’s optimism about helping patients with mental disorders and in their confidence in their ability to diagnose mental disorders following the intervention. There was no statistically significant change in GP’s interest in patients with mental disorders or in their reporting of the importance of diagnosing mental disorders.Pagaiya and Garner [41]ThailandPhysical health (diabetes mellitus) and mental health (anxiety and panic disorder)Cluster randomised controlled trialModerate risk of bias CPG Four clinical guidelines introduced: two for children (acute respiratory infection and diarrhoea); two for adults (diazepam prescribing for anxiety and panic disorder and management of diabetes mellitus) Setting and participants Health centres in Khon Kaen province in Thailand, mainly in rural areas. 9 health centres were randomised to receive the intervention and 9 to control.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ICD-10 training kit, an educational training programme and materials produced by the WHOImplementation strategies therefore comprised: educational meetings and educational materialsGP’s attitudes, knowledge, interview skills and ability for diagnosing psychiatric disorders in a primary care settingThere was statistically significant improvement in GP’s optimism about helping patients with mental disorders and in their confidence in their ability to diagnose mental disorders following the intervention. There was no statistically significant change in GP’s interest in patients with mental disorders or in their reporting of the importance of diagnosing mental disorders.Pagaiya and Garner [41]ThailandPhysical health (diabetes mellitus) and mental health (anxiety and panic disorder)Cluster randomised controlled trialModerate risk of bias CPG Four clinical guidelines introduced: two for children (acute respiratory infection and diarrhoea); two for adults (diazepam prescribing for anxiety and panic disorder and management of diabetes mellitus) Setting and participants Health centres in Khon Kaen province in Thailand, mainly in rural areas. 9 health centres were randomised to receive the intervention and 9 to control.…”
Section: Resultsmentioning
confidence: 99%
“…Four of these papers related to the introduction of CPGs for non-communicable diseases in physical health [3740], one paper included CPGs for both a non-communicable disease in physical health and mental health [41] and one paper examined the introduction of a CPG for mental health [42]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Unnecessary use of antibiotics is seen among both health professionals and the public. [9][10][11][12] In European countries, systemic antibiotics are prescribed in the greatest volumes to ambulatory patients, mostly for respiratory tract infections. 13 In Thailand, a study in a tertiary care hospital revealed that only 7.9% of the upper respiratory tract infections (URIs) in the facility were caused by bacteria.…”
Section: Introductionmentioning
confidence: 99%